PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE WRITE AROUND BERBANTUAN MEDIA GAMBAR BERSERI TERHADAP KEMAMPUAN MENULIS PROSA SISWA KELAS V SD - Ayuningtyas, Risty Amaria; Hanindita, Amelia Widya (Universitas Negeri Medan, 2025)
Based on initial observations, students had low writing skills, leading to a lack of active participation in writing lessons. This study aims to describe the effect of the cooperative learning model write around, supported by sequential image media, on the writing skills of fifth-grade elementary students. It is a quantitative study using an experimental method with a quasi-experimental design and a nonequivalent control group framework. The population consists of fifth-grade students at SDN Sumur Welut III/440 Surabaya, with a sample of 32 students divided into experimental and control groups. Data were collected using essay-type tests. The research results reveal that the implementation of the cooperative learning model type Write Around, supported by serial picture media, influences the prose writing skills of fifth-grade students. This statement refers to the hypothesis test results indicating a sig value of 0.001<0.05, meaning H0 is rejected and H1 is accepted. Additionally, the experimental class's average pretest-posttest increase is 28.5, superior to the control class's 20.25. Therefore, the write around model, supported by picture series media, positively affects students' prose writing skills.